2023
DOI: 10.3389/fimmu.2023.1097403
|View full text |Cite
|
Sign up to set email alerts
|

NCAPG2 could be an immunological and prognostic biomarker: From pan-cancer analysis to pancreatic cancer validation

Abstract: More recently, NCAPG2 has emerged as an intrinsically essential participant of the condensin II complex involved in the process of chromosome cohesion and stabilization in mitosis, and its position in particular tumours is now being highlighted. Simultaneously, the genetic properties of NCAPG2 hint that it might have enormous potential to interpret the malignant progression of tumors in a broader perspective, that is, in pan-cancer. Yet, at present, this recognition remains merely superficial and there is a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…This gene encodes for a regulatory subunit of the condensin II complex which, along with the condensin I complex, plays a role in chromosome assembly and segregation during mitosis [35]. Alterations of this gene have been associated with cancer and neurodevelopmental defects [36, 37], and although its presence has already been observed in PD blood transcriptomics [38, 39], its role in the disease is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This gene encodes for a regulatory subunit of the condensin II complex which, along with the condensin I complex, plays a role in chromosome assembly and segregation during mitosis [35]. Alterations of this gene have been associated with cancer and neurodevelopmental defects [36, 37], and although its presence has already been observed in PD blood transcriptomics [38, 39], its role in the disease is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent research has acknowledged the growing importance of gene in the development of cancer. Wang et al proposed that NCAPG2 could potentially function as a regulatory element and a biomarker for various malignancies [32]. Li et al demonstrated that EIF4G1 may have the ability to modify the tumor microenvironment and inhibit the metastasis of Breast cancer (BRCA), thus potentially serving as a prognostic biomarker and therapeutic target for BRCA [33].…”
Section: Discussionmentioning
confidence: 99%
“…The R package “forest” displayed the results of the prognostic analysis. The Kaplan–Meier (K-M) plots evaluated patient survival status in specific cancers with the R packages “survival” (for statistical analysis) and “survminer” (for visualization) [ 26 , 27 ]. In addition, we assessed the association between WDHD1 expression and patient prognosis using the PrognoScan database ( http://www.prognoscan.org/ ) and independent datasets from the Gene Expression Omnibus (GEO) database ( https://www.ncbi.nlm.nih.gov/geo/ ) [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%